2020
DOI: 10.3390/coatings10040390
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Nanoparticles Coated upon Silver Hollow Nanosphere as an Integrated Design to Reinforce SERS Detection of Trace Ampicillin in Milk Solution

Abstract: Surface-enhanced Raman scattering (SERS) technique is competent to trace detection of target species, down to the single molecule level. The detection sensitivity is presumably degraded by the presence of non-specific binding molecules that occupy a SERS-active site (or hot spot) on the substrate surface. In this study, a silver hollow nano-sphere (Ag HNS) with cavity has been particularly designed, followed by depositing dielectric nanoparticles (Di NPs) upon Ag HNS. In the integrated nanostructures, Di NPs/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The performance of other representative SERS sensors toward ampicillin determination in DI water is summarized in Table 1. 42–47 The LOD of our SERS fabric substrate for ampicillin (1.3 μM) detection using a handheld Raman spectrometer was higher than those of the previously reported SERS substrates using a Raman microscope. It is because a Raman microscope coupled with an objective lens with higher magnification (100× or 50×) offers great SERS signal amplification than a portable one with lower magnification objective lenses (<5×).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The performance of other representative SERS sensors toward ampicillin determination in DI water is summarized in Table 1. 42–47 The LOD of our SERS fabric substrate for ampicillin (1.3 μM) detection using a handheld Raman spectrometer was higher than those of the previously reported SERS substrates using a Raman microscope. It is because a Raman microscope coupled with an objective lens with higher magnification (100× or 50×) offers great SERS signal amplification than a portable one with lower magnification objective lenses (<5×).…”
Section: Resultsmentioning
confidence: 67%
“…It is because a Raman microscope coupled with an objective lens with higher magnification (100× or 50×) offers great SERS signal amplification than a portable one with lower magnification objective lenses (<5×). 13,48–50 However, our SERS substrate with a handheld Raman spectrometer can possibly be used for fast-screening and onsite detection.…”
Section: Resultsmentioning
confidence: 99%
“…The sensors are able to determine the dielectric properties of food by resonance frequency (Amar et al., 2020). This method has led to the amount of rare particles present in food such as ampicillin (Lee et al., 2020). The results also determined that among nutrients, protein has the greatest effect on the dielectric properties of milk (Zhu et al., 2014), but these results do not have the same answer at all frequencies because in (Abdullah et al., 2019) has been showed that at different frequency bands these results may change and many factors are involved in this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the advantages and limitations of SERS technology in comparison to other diagnostic methods, it is also important to emphasize that since a SERS-active substrate, the main component, is comprised of a plasmonic metal or a dielectric material ( Lee et al, 2020 ; Sitjar et al, 2019 ); it needs not be used urgently as it is stable and thus could be stored for a long time, given that a proper storage condition and environment are followed. Processes involved in the fabrication of substrates are thus crucial in coming up with an effective SERS-active substrate.…”
Section: Introductionmentioning
confidence: 99%